BLAME-FRAME AND PRAISE-FRAME ON THE BOKO HARAM TERRORISM IN NIGERIA NEWSPAPERS: A DISCOURSE EXAMINATION - Osisanwo, Ayo (PEOPLE: International Journal of Social Sciences, 2019)
Boko Haram, as reported by the media, has been terrorising Nigeria, especially since 2009. Linguistic studies on terrorism and Boko Haram in Nigeria have considered, among others, the representations of the group by the media and policy makers. However, insufficient discourse attention has been devoted to the framing tactics deployed by social actors in identifying the roles played by two administrations in the escalation or denigration of Boko Haram terrorism in Nigeria. Yet, the consideration can lend further insights into the Boko Haram operations, and identifying the possible failures and successes in curbing the menace in Nigeria. Therefore, this paper examines the strategies deployed by social actors (political, religious and ethnic) as reported by selected newspapers to identify the roles played by two administrations in the State, Nigeria. For data, different utterances on the blame-praise frames, credited to different social actors are purposively selected from the electronic versions of newspapers from 2013 to 2017 (two years each from two administrations). Guided by aspects of critical discourse analysis, with bias for van Dijk’s ideological structures, the study revealed that there are two broad frames on the administrations: blame-frame and praise-frame. The blame-frame strategies include blame-frame as propaganda tactic, finger-pointing and demonization strategy, justification for political migration, buck passing, and social-control technique. The praise-frame strategies include praise-frame for ventilation and behavioural reinforcement, strengthening bilateral relations, proof of change actualization, and self-praise. The frames are reinforced with sixteen ideological discourse structures, including ’actor description’, ’authority’, ’categorisation’, among others.